Stem progenitor cells in the human pancreas - Giorgia Locci; Anna Paola Pinna; Angelica Dessì; Eleonora Obinu; Clara Gerosa; Maria Antonietta Marcialis; Maria Cristina Pintus; Marco Angiolucci; Vassilios Fanos; Rossano Ambu; Gavino Faa (Hygeia Press di Corridori Marinella, 2016)
Early pancreas development, given its complexity, is generally considered as a paradigm for branching morphogenesis and for the development of two organs in one: the Langherans islets, programmed to secrete hormones into the bloodstream, and the exocrine pancreas compartment, composed of two major cell types, acinar and ductal cells, devoid to secrete digestive enzymes into the duodenum through a branched network of ducts. Exocrine and endocrine pancreas are generally presumed to originate from a common multi-lineage progenitor cell (MPC), emerging within the definitive endoderm surrounding the posterior foregut. Bipotential precursors committed to the pancreatic fate originate the MPC, that are considered the progenitors of all pancreatic cells operating in the mature pancreas, including acinar, ductal, endocrine and stromal cell types. Pluripotent stem cells (PSCs) are able to differentiate into several cell types, including acinary cells, duct cells and islet cells, depending on certain transcription factors, which function in a coordinated way during pancreas development. The epidemiological entity of pancreatic diseases such as diabetes mellitus and issues regarding the management of the diabetic patient have constantly stimulated the great current interest aimed at regenerative pancreatic medicine. Several studies in rats have demonstrated the existence of stem/progenitor cells in the adult pancreas and have clarified the mechanism by which pancreatic stem cells differentiate into acinar, ductal and endocrine cells. In this context, the cellular microenvironment called "niche" plays a major role in inducing differentiation of stem/progenitor cells by adequate cellular signals. Within the niche, undifferentiated pluripotent cells give rise to asymmetrically dividing daughter cells. The main purpose of this work was to identify stem cells and progenitor cells in the human pancreas during intrauterine development in relation to what is already known in the adult pancreas and in experimental models.   Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano